FRI0150 USEFULNESS OF SALIVARY GLAND ULTRASONOGRAPHY IN THE ASSESSMENT OF SALIVARY GLAND ACTIVITY AND DAMAGE IN PRIMARY SJÖGREN'S SYNDROME: A SINGLE CENTER EXPERIENCE. (2nd June 2020) - Ferro, F.; Governato, G.; Donati, V.; Fulvio, G.; Fonzetti, S.; Elefante, E.; Luciano, N.; Mosca, M.; Cecchettini, A.; Baldini, C.
Abstract : Background: Salivary gland ultrasonography (SGUS) has an emerging role in the diagnosis of primary Sjögren's syndrome (pSS); however, it is still an open issue whether distinct sonographic abnormalities may indicate reversible glandular activity or irreversible disease-induced damage. Objectives: to assess the association between SGUS abnormalities, salivary gland disease activity and loss of function in pSS patients over a long-term follow-up. Methods: Patients with pSS fulfilling the AECG 2002 criteria were included in this observational study. Both parotid and submandibular glands were examined at the time of the study inclusion and during the follow-up. SGUS findings (i.e gland size, echogenicity, homogeneity, hyperechoic bands, number and location of the hypoechoic/anechoic areas, number of lymph nodes, calcification, posterior border visibility) were defined according to previous studies and monitored over the time. Patients demographics, clinical, histological and laboratory data were routinely collected. ESSDAI and ESSPRI were used to asses disease activity and PROs. Results: We included 419 (402 F:17 M) pSS patients: 206/419 at the diagnosis and 213/419 with a median disease duration of 7 (IQR 4-11) years. SGUS examination was repeated in 81/206 and in 108/213 patients, after a median follow-up of 30 (IQR 12-42) months, respectively. Noteworthy, 18/419 pSS patients were treated with rituximab (RTX) during the study period. The overall SGUS score correlated directly with the minor salivary focus score (r=0.366, p=0.000) and with the ESSDAI (r=0.482, p=0.000); the parotid inhomogeneity score correlated directly with the glandular domain of the ESSDAI (r=0.530, p=0.000). The unstimulated salivary flow rate (USFR) correlated inversely with the overall SGUS score (r=-257, p=0.000) and with the presence of hyperechoic bands in both the parotid (r=-210, p=0.03) and the submandibular glands (r=-316, p=0.000). When compared to patients with an established pSS, newly diagnosed patients presented less frequently a gross inhomogeneity in their parotid glands (30/206, 14.6% vs 53/213, 24.9%, p=0.01) and less hyperechoic bands in both their parotid (33/206, 16% vs 61/213, 29%, p=0.001) and submandibular glands (53/206, 26% vs 110/213, 52%, p=0.001). However, over a median 30 month-follow-up we did not observe any significant change neither in the number of hypo-anechoic areas nor in the inhomogeneity score in both newly diagnosed patients and in those with an established disease. Out of the 18 pSS patients treated with RTX, 14 (78%) presented at the baseline a moderate to gross inhomogeneity in their glands: no changes in the number of hypo-anechoic areas were observed also in these patients with the exception of a variation in the number of intra-parotid lymph nodes. Conclusion: SGUS abnormalities appeared to be associated to both salivary gland disease activity and damage. Namely, the presence of hyperechoic bands significantly correlated with salivary loss function. Diffuse-scattered hypoechoic areas did not change over a median 30-month followed-up indicating that additional studies are required to better elucidate the correlation between SGUS abnormalities and the corresponding histopathologic lesions. Disclosure of Interests: Francesco Ferro: None declared, Gianmaria Governato: None declared, Valentina Donati: None declared, Giovanni Fulvio: None declared, Silvia Fonzetti: None declared, Elena Elefante: None declared, Nicoletta Luciano Speakers bureau: Paid as speaker for Eli Lilly, Sanofi, Marta Mosca: None declared, Antonella Cecchettini: None declared, Chiara Baldini: None declared